A the FACTORS RELATED TO THE FATIGUE OF ONLINE MOTORCYCLE TAXI WORKERS IN CIPAYUNG DISTRICT, EAST JAKARTA IN 2021: FACTORS RELATED TO THE FATIGUE OF ONLINE MOTORCYCLE TAXI WORKERS IN CIPAYUNG DISTRICT, EAST JAKARTA IN 2021 - handayani, fitri (Muhammadiyah International Public Health and Medicine Proceeding, 2022)
Traffic accidents in Indonesia are still one of the most significant contributors to the death rate caused by accidents of online motorcycle taxi workers caused by fatigue. Although Indonesia is ranked third in the data, judging from the statistical percentage of the total population, Indonesia is ranked first with a mortality rate of 0.015 percent of the total population, below China with a ratio of 0.018 percent and India with 0.017. The general purpose of this study is to find out the factors related to the willingness of online motorcycle taxi workers in Cipayung District, East Jakarta, in 2021.   The method used to measure fatigue in online motorcycle taxi workers uses a Quantitative design with a cross-sectional way.   Fatigue is a state that is accompanied by a decrease in performance and endurance in working with the primary sources of visible fatigue, physical fatigue, emotional fatigue, fatigue due to the environment itself, as well as fatigue and an environment that does not heal as a fact.   There is no relationship between sex and age with fatigue (P > 0.05). There is a relationship between the length of work and quality of sleep with fatigue (P <0.05). From the data, it is stated that two variables say that there is a relationship between long work, Julieta sleeps with the willingness of online motorcycle taxi workers in Cipayung District, East Jakarta, in 2021.